Comparative Analysis of Rehabilitation Approaches for Pencak Silat Injuries: Evidence from Thailand and Iran - Dedi Pirdaus; Somchanok Hongthong; Afsaneh Sheykhi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study aims to compare sports injury rehabilitation approaches in Thailand and Iran, particularly the effectiveness of Swedish massage, hot compress therapy, and stretching for reducing pain and improving range of motion among adolescent martial arts athletes with upper limb injuries. Methodology: This study employed a comparative qualitative review design using sports rehabilitation literature from Thailand and Iran. Data were collected from journal articles, experimental rehabilitation studies, physiotherapy reports, and sports medicine publications. Comparative thematic analysis was applied to evaluate Swedish massage, hot compress, and stretching interventions for adolescent combat sport injury rehabilitation. Main Findings: The findings showed that Swedish massage was more effective for pain reduction, while hot compress therapy provided superior range of motion recovery. Thailand demonstrated stronger standardized physiotherapy implementation and institutional rehabilitation systems, whereas Iran emphasized individualized athlete-centered recovery approaches. Early adolescent athletes in both countries showed faster rehabilitation responsiveness compared to late adolescents. Novelty/Originality of this Study: This study provides a cross-country comparative perspective on martial arts injury rehabilitation by examining how therapeutic approaches and rehabilitation systems differ across Thailand and Iran. The novelty lies in integrating clinical rehabilitation perspectives with contextual differences in healthcare systems, athlete management, and treatment approaches to propose a more comprehensive framework for Pencak Silat injury rehabilitation.